Ultrastructural Examination of the Corneal Interface after Predescemetic Deep Anterior Lamellar Keratoplasty (DALK) – A Case Report with Light and Transmission Electron Microscopy - Berger, Tim; Seitz, Berthold; Hamon, Loïc; Flockerzi, Fidelis; Schlötzer-Schrehardt, Ursula; Daas, Loay (Klinische Monatsblätter für Augenheilkunde, 2022)
Purpose To examine corneal buttons with light and transmission electron microscopy (TEM) to visualize the interface area and highlight the ultrastructural corneal changes after deep anterior lamellar keratoplasty (DALK).Methods Two patients underwent excimer laser-assisted penetrating repeat keratoplasty after predescemetic DALK. The corneal buttons were examined by light microscopy and TEM.Results The light microscopic examination of the corneal buttons revealed fragments of a second Descemetʼs membrane in the central and midperipheral areas (Case 1). In both cases, visualization of the interface area was not possible by light microscopy. The donor and host stroma were tightly attached without dehiscence. TEM identified the interface area by irregularities in the collagen distribution between the donor and host stroma. The thickness of the remaining recipient corneal stroma measured approximately 30 µm (Case 1) and 100 µm (Case 2), respectively. In the host stroma, TEM revealed the absence or degeneration of keratocytes, accumulation of amorphous material between the collagen lamellae, and vacuolar inclusions dispersed in the stroma, forming a band-like zone anterior to Descemetʼs membrane.Conclusion The interface area after DALK has been mainly investigated by in vivo confocal microscopy. Light microscopy and TEM findings indicate remodeling processes after DALK that are associated with increased keratocyte degeneration and structural alterations of the extracellular matrix in the host stroma. The choice of surgical method may influence the postoperative morphological and functional outcome since these findings were primarily apparent in the remaining host stroma. Therefore, complete exposure of Descemetʼs membrane is an important prognostic factor for the postoperative visual outcome.
Keywords: deep anterior lamellar keratoplasty; penetrating keratoplasty; light microscopy; transmission electron microscopy; interface; DALK